2021
DOI: 10.3390/brainsci11060689
|View full text |Cite
|
Sign up to set email alerts
|

Societal Cost of Ischemic Stroke in Romania: Results from a Retrospective County-Level Study

Abstract: Background: Health policies in transitioning health systems are rarely informed by the economic burden of disease due to scanty access to data. This study aimed to estimate direct and indirect costs for first-ever acute ischemic stroke (AIS) during the first year for patients residing in Cluj, Romania, and hospitalized in 2019 at the County Emergency Hospital (CEH). Methods: The study was conducted using a mixed, retrospective costing methodology from a societal perspective to measure the cost of first-ever AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…An opportunity to explore this topic will emerge upon completion of the C-REGS 2 registry study [45]. Nevertheless, based on incident strokes reported by the Romanian Society of Neurology in 2022 (n = 37.225), a gross assumption that around 80% of cases would fit the ischemic indication [46], and of those, two-thirds of cases would be moderate-severe and hence, eligible for Cerebrolysin treatment, the incremental cost difference from our study (408 EUR) and the estimated budget impact of treating acute stroke patients for 21 days with Cerebrolysin in line with the CARS protocol would be roughly 8.5 million EUR per year, assuming the intervention would not currently exist on the market, which is around 5% of the healthcare economic burden of stroke in the country [43,47]. In addition to this proportionally small estimated budget impact (which we stress is likely overestimated in such gross calculations), given that overall stroke expenditure in Romania is up to tenfold less than other countries in Europe and the current increasing trend of expenditure at the national level [46,48], we assert that the normalization of Cerebrolysin treatment in line with the CARS protocol would entail a manageable budget impact for the Romanian healthcare system.…”
Section: Qalys)mentioning
confidence: 83%
See 1 more Smart Citation
“…An opportunity to explore this topic will emerge upon completion of the C-REGS 2 registry study [45]. Nevertheless, based on incident strokes reported by the Romanian Society of Neurology in 2022 (n = 37.225), a gross assumption that around 80% of cases would fit the ischemic indication [46], and of those, two-thirds of cases would be moderate-severe and hence, eligible for Cerebrolysin treatment, the incremental cost difference from our study (408 EUR) and the estimated budget impact of treating acute stroke patients for 21 days with Cerebrolysin in line with the CARS protocol would be roughly 8.5 million EUR per year, assuming the intervention would not currently exist on the market, which is around 5% of the healthcare economic burden of stroke in the country [43,47]. In addition to this proportionally small estimated budget impact (which we stress is likely overestimated in such gross calculations), given that overall stroke expenditure in Romania is up to tenfold less than other countries in Europe and the current increasing trend of expenditure at the national level [46,48], we assert that the normalization of Cerebrolysin treatment in line with the CARS protocol would entail a manageable budget impact for the Romanian healthcare system.…”
Section: Qalys)mentioning
confidence: 83%
“…However, only a few hospitals can perform endovascular thrombectomy (EVT) for stroke patients, while the rest can only conduct intravenous thrombolysis. Notably, most hospitals are not meeting comprehensive stroke unit standards, as defined by the European Stroke Organization (ESO) [43]. From 2015 to 2018, around 1800 patients received reperfusion treatment through the PAS program, as reported by the Romanian Ministry of Health.…”
Section: Qalys)mentioning
confidence: 99%
“…On the other hand, some studies, such as the one in Turkey by Asil et al [ 23 ], in Pakistan by Khealani et al [ 24 ], in Cameroon by Njankouo et al [ 25 ], in Malaysia by Nor Azlin et al [ 26 ], and in Senegal by Touré et al [ 9 ], found too low costs: $1677, $1179, $1543, $807, and $416, respectively. In contrast, a study by Strilciuc et al in Romania reported a higher cost of stroke care at $5226.82 [ 27 ]. The difference in the cost estimates among these studies may be due to the method used to estimate the cost of stroke care; for instance, Nor Azlin et al adopted a top-down costing approach with a global vision that did not take into account the patient's share of spending (out-of-pocket) [ 26 ].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, using a mapping algorithm, the results were compared with the values for the quality of life from other studies [ 9 ]. The direct and indirect costs of stroke have been assessed in Romania, and found to be dominated by direct costs [ 10 , 11 ], with important cost differences between post-stroke therapies [ 12 ]. Economic evidence is not sufficient to support policy decisions to fund new interventions and a need exists for of quality of life (QoL) evaluation.…”
Section: Introductionmentioning
confidence: 99%